Penanggulangan Kemiskinan Perempuan melalui Strategi Keuangan Inklusif oleh Koperasi Mitra Dhuafa (KOMIDA) - Saragih, Junius Fernando S. (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2020)
Poverty is still relatively high, especially among women. On the one hand the gap in work participation between men and women still occurs. On the other hand women have the opportunity to overcome the problems of poverty and their families with flexible work and do not interfere with the task of taking care of the household. Entrepreneurship is the right choice but needs to be accompanied by inclusive finance that brings capital closer to women. Inclusive finance is characterized by access to business capital financing without collateral, one-stop financial transactions, availability of financing that exceeds demand and increased financial literacy including saving habits and increasing financial management capabilities. It aims to describe and analyze the application of inclusive financial strategies in sustainable poverty reduction for women and to explain and analyze the impact of poverty reduction on low-income women and their families. The research method used is a qualitative approach with a descriptive type. The results show that financing can increase business interest and stimulate business development, increase income and strengthen the role of women in the welfare of their families. Poverty alleviation through an inclusive financial strategy is effective in increasing the economy, capacity and role of women in the welfare of the family. An adequate selection and monitoring system has a profound effect on this success.AbstrakKemiskinan masih tergolong tinggi, khususnya di kalangan perempuan. Sementara kesenjangan partisipasi kerja antara laki-laki dan perempuan masih terjadi. Di sisi lain perempuan memiliki peluang untuk mengatasi masalah kemiskinannya dan keluarganya dengan pekerjaan yang fleksibel dan tidak mengganggu tugas mengurus rumah tangga. Berwirausaha adalah pilihan yang tepat, namun perlu diiringi dengan keuangan inklusif yang mendekatkan modal kepada perempuan. Keuangan inklusif ditandai dengan akses terhadap pembiayaan modal usaha tanpa agunan, transaksi keuangan satu pintu, ketersediaan pembiayaan yang melebihi permintaan, dan peningkatan literasi keuangan, meliputi kebiasaan menabung serta peningkatan kemampuan pengelolaan keuangan. Penelitian ini bertujuan menguraikan dan menganalisis penerapan strategi keuangan inklusif dalam penanggulangan kemiskinan perempuan serta dampaknya terhadap perempuan berpendapatan rendah dan keluarganya. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan jenis deskriptif. Hasil menunjukkan bahwa pembiayaan mampu meningkatkan minat usaha dan memberi stimulan dalam pengembangan usaha, peningkatan pendapatan, serta memperkuat peran perempuan dalam menyejahterakan keluarganya. Penanggulangan kemiskinan melalui strategi keuangan inklusif efektif meningkatkan ekonomi, kapasitas dan peran perempuan dalam menyejahterakan keluarga. Sistem seleksi dan monitoring yang memadai sangat besar pengaruhnya akan keberhasilan ini.